THE LEGAL ANALYSIS OF “TEORI KEDAULATAN NUSANTARA” TOWARDS THE NEW CONCEPTION OF INDONESIA AIRSPACE SOVEREIGNTY - Kusumaningrum, Adi (UI Scholars Hub, 2017)
Art. 1 Chicago Convention of 1944 confirms that every state has a complete and exclusive sovereignty over the airspace above its territory. This arrangement gives the highest role of state in controlling air transportation based on state sovereignty principles. The concept of airspace sovereignty faced challenges with the introduction of international air transportation liberalization through deregulation provisions. Such liberalization policy is later known as ‘open sky policy’. Such open sky policy includes the establishment of single market such as Single European Sky dan ASEAN Single Aviation Market. The liberalization led to a situation where sovereignty concept has been regarded from a different perspective. It is widely argued that the smooth operation of new forms of international cooperation requires a more flexible perception of sovereignty. This study wants to analyze the concept of Indonesia airspace sovereignty. A theory of Indonesia airspace sovereignty that ever born is the